Change and Diversity in Neolithic Mortuary Practices on the Isle of Man. (21st December 2021) - Fowler, Chris; Crellin, Rachel J.; Gamble, Michelle
Abstract : While the Early Neolithic chambered tombs of the Isle of Man are well known and the Late Neolithic has been clearly defined with reference to a distinctive suite of artefacts, little is known about the Middle Neolithic. This article reports on 17 new Neolithic radiocarbon dates from cremated human remains from the Isle of Man. These identify five burials in cists as Middle Neolithic and indicate new sequences of activity at cemeteries starting in the Middle Neolithic. Each of these sites is examined in detail. The dates also spur a reconsideration of the development of Ronaldsway pottery and the integration of Grooved Ware pottery and motifs into early 3rd millennium practice on the island. The paper ends with a consideration of the changing effects of mortuary practices throughout the Neolithic on the Isle of Man and a discussion of connections with Middle and Late Neolithic activity in Ireland and Britain.